(untitled) (Politeja, 2021)
The article describes life and political ideas of Aleksander Trzaska‑Chrząszczewski, one of the most distinctive political scientists and conservative thinkers of the interwar period in Poland. The essay contains many – earlier unknown – biographical details and Chrząszczewski’s political, international and historiosophic conceptions. In his essays Chrząszczewski criticised political system based on the democratic constitution from 1921 and political practise of authoritarian regime ruled after 1926 r. He precisely pointed out inconsistency of Pilsudski’s camp, which declared strengthening of the State as an aim of political activity and on the other hand very often ruled by informal instruments. In the international relations’ area Chrząszczewski was a follower of pro-French orientation. He observed evolution of German political system during Nazi regime and warned against rising of political and military power of Third Reich. Przypływy i odpływy demokracji (The Tides of Democracy), written in 1939, is still the most recognizable Chrząszczewski’s work. The Author proposed original vision of political changes stimulated by increasing or decreasing activity of masses. Chrząszczewski’s theory is one of the most interesting attempts to analyze social and political events of 1930s, that could be compared with the ones made by José Ortega y Gasset or Florian Znaniecki.